Differential effects of the essential oils of Lavandula luisieri and Eryngium duriaei subsp. juresianum in cell models of two chronic inflammatory diseases - Rufino, AT (2015)
CONTEXT: Effective drugs to treat osteoarthritis (OA) and inflammatory bowel disease (IBD) are needed. OBJECTIVE: To identify essential oils (EOs) with anti-inflammatory activity in cell models of OA and IBD. MATERIALS AND METHODS: EOs from Eryngium duriaei subsp. juresianum (M. Laínz) M. Laínz (Apiaceae), Laserpitium eliasii subsp. thalictrifolium Sennen & Pau (Apiaceae), Lavandula luisieri (Rozeira) Rivas-Martínez (Lamiaceae), Othantus maritimus (L.) Hoff. & Link (Asteraceae), and Thapsia villosa L. (Apiaceae) were analyzed by GC and GC/MS. The anti-inflammatory activity of EOs (5-200 μg/mL) was evaluated by measuring inducible nitric oxide synthase (iNOS) and nuclear factor-κB (NF-κB) activation (total and phosphorylated IκB-α), in primary human chondrocytes and the intestinal cell line, C2BBe1, stimulated with interleukin-1β (IL-1β) or interferon-γ (IFN-γ), IL-1β and tumor necrosis factor-α (TNF-α), respectively. RESULTS: The EO of L. luisieri significantly reduced iNOS (by 54.9 and 81.0%, respectively) and phosphorylated IκB-α (by 87.4% and 62.3%, respectively) in both cell models. The EO of E. duriaei subsp. juresianum caused similar effects in human chondrocytes, but was inactive in intestinal cells, even at higher concentrations. The EOs of L. eliasii subsp. thalictrifolium and O. maritimus decreased iNOS expression by 45.2 ± 8.7% and 45.2 ± 6.2%, respectively, in C2BBe1 cells and were inactive in chondrocytes. The EO of T. villosa was inactive in both cell types. DISCUSSION AND CONCLUSION: This is the first study showing anti-inflammatory effects of the EOs of L. luisieri and E. duriaei subsp. juresianum. These effects are specific of the cell type and may be valuable to develop new therapies or as sources of active compounds with improved efficacy and selectivity towards OA and IBD.